Maintainability analysis of Consumer Electronics using Software Quality Metrics (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Software quality is a complex mix of factors that will very across different application and the customers who request them [1]. Determining the quality of products so ftware quality is important factor in consumer electronic software. Consumer electronics domain demands high performance, low cost and easy to use continuous need for new product innovation. So, maintainability is considered as a solution to satisfying such demand. Maintainability is an important quality goal for CE product software. In this paper, we have identified some quality characteristics of McCall as critical quality factors, these factor help in our model to improve the quality of product in busine ss and define the product properties. Also we have identified metrics which can be measured by static analysis tool (veracode, codesonar) for critical quality factors and then,we found some problems which affect the software quality. We design a model for CE products, derived quality model can be utilized for quality evaluation and quality improvement in CE domain.